2018
DOI: 10.1177/1534735418775809
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Clinical Experience With Intravenous Ascorbic Acid in Patients With Cancer

Abstract: Background. Intravenous ascorbic acid (IV AA) has been used extensively in cancer patients throughout the United States. Currently, there are limited data on the safety and clinical effects of IV AA. The purpose of this study was to expand the current literature using a retrospective analysis of adverse events and symptomatic changes of IV AA in a large sample of cancer patients. Methods. We conducted a retrospective chart review of all patients receiving IV AA for cancer at the Thomas Jefferson University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In 8 studies, vitamin C was given intravenously (IV), all in different doses and time intervals [22,25,26,27,28,33,35,37]. In 8 studies intravenous vitamin C (IVC) was given followed by or in combination with oral vitamin C supplementation [1,2,23,24,30,31,34,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 8 studies, vitamin C was given intravenously (IV), all in different doses and time intervals [22,25,26,27,28,33,35,37]. In 8 studies intravenous vitamin C (IVC) was given followed by or in combination with oral vitamin C supplementation [1,2,23,24,30,31,34,36].…”
Section: Resultsmentioning
confidence: 99%
“…In 7 studies, conventional anti-cancer treatment was given in addition to the administration of vitamin C [22,24,25,27,34,35,37]. In 6 studies, this was not specifically documented, but it seems unlikely that patients had concomitant treatments [3,26,28,30,32,36] and in 6 articles it was written that no additional treatment was given at the time of the intervention with vitamin C [1,2,23,29,31,33].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin C as an immunomodulatory nutrient with a strong potential against gastrointestinal damage induced by antineoplastic drugs 42 and is also able to contribute to the reduction of symptom severity 43,44 , which could explain gradual weight loss throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, intravenous pharmacological ascorbate is now in wide use by the American public . Extensive literatures and clinical trials revealed that pharmacological ascorbate could be a promising chemotherapeutic drug for cancer patients . Recent clinical trials also showed that it is a potential adjuvant to improve the efficacy of standard cancer therapy in ovarian, brain cancer, and lung cancer patients .…”
Section: Methodsmentioning
confidence: 99%